Dietary predictors and plasma concentrations of perfluorinated alkyl acids in a Singapore population. (March 2017) - Liu, Yu; Su, Jin; van Dam, Rob M.; Prem, Kiesha; Hoong, Joey Y.S.; Zou, Li; Lu, Yonghai; Ong, Choon Nam
Abstract: Perfluorinated alkyl acids (PFAAs), a family of man-made organofluorinated compounds, have drawn much attention due to their ubiquitous existence in the environment and their bioaccumulation potential. Here, we examined the plasma concentrations of thirteen PFAAs in a healthy population (N = 270) in Singapore, and investigated the association between major food groups and plasma PFAA concentrations. We detected eight types of PFAAs in more than 75% of all samples (N = 270), and their median concentrations ranged from 0.05 to 8.34 ng mL −1 . Age- and gender-related differences were observed for the three dominant PFAAs, i.e., perfluorooctanesulfonic acid (PFOS), perfluorohexane sulfonate (PFHxS) and perfluorooctanoate acid (PFOA), with concentrations being higher in men and older adults. Multiple linear regression analyses showed that fish, shellfish, red meat and poultry were associated with increased PFAAs concentrations in plasma, whereas grains and soy products showed inverse associations with PFAAs. Further, significant correlations were observed between various long-chain PFAAs and plasma concentrations of omega-3 fatty acids, suggesting seafood was a significant source of these PFAAs, within this population. Future studies on diet exposure to PFAAs are encouraged to focus more on the effects on diet pattern. Highlights: 13 PFAAs in 270 plasma samples from Singapore Prospective Study Program were analyzed. Intakes of seafood and meat were associated with increased PFAAs, whereas grains and soy products had inverse associations. Plasma Omega-3 fatty acids were correlated with various long-chain PFAAs.